Eco-friendly synthesis of a novel magnetic Bi4O5Br2/SrFe12O19 nanocomposite with excellent photocatalytic activity and recyclable performance. Issue 6 (15th March 2021) - Wang, Hailong; Xu, Longjun; Wu, Xin; Zhang, Maojie
Abstract: To improve the catalytic activity and recovery efficiency of photocatalysts, the Bi4 O5 Br2 was decorated on SrFe12 O19 via a microemulsion method to synthesize a novel magnetic Bi4 O5 Br2 /SrFe12 O19 nanocomposite. The microstructures, morphological characteristics, photoelectrochemical properties, magnetic performance and photocatalytic mechanism of catalysts were investigated by various techniques. The photocatalytic experiments presented that the Bi4 O5 Br2 /SrFe12 O19 photocatalyst with 5 wt% of SrFe12 O19 has the best capacity for degrading Rhodamine B (RhB). The activity of the photocatalyst was increased by the optimization of energy band structure and the formation of an internal electric field in the type-II heterojunction. Moreover, the h + and ·O2 - were demonstrated to be the primary active constituents in the photocatalytic reaction by the energy-band structure analysis and radical scavenging experiments. The saturated magnetizing strength (Ms) and the recovery rate of composite photocatalyst were 2.76 emu·g −1 and 88.2% respectively, which confirmed that the nanocomposite has excellent magnetic property. Meanwhile, the photodegradation rate was still 84.6% after five circulating tests, which demonstrated that the sample has the superior photo-stability performance. This paper offers a new approach to the synthesis of the composite magnetic photocatalyst based on Bi4 O5 Br2, and some guidance for the photocatalytic degradation mechanism.